2016
DOI: 10.1111/bcp.12975
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility and effect of deprescribing in older adults on mortality and health: a systematic review and meta‐analysis

Abstract: AIMSDeprescribing is a suggested intervention to reverse the potential iatrogenic harms of inappropriate polypharmacy. The review aimed to determine whether or not deprescribing is a safe, effective and feasible intervention to modify mortality and health outcomes in older adults. METHODSSpecified databases were searched from inception to February 2015. Two researchers independently screened all retrieved articles for inclusion, assessed study quality and extracted data. Data were pooled using RevMan v5.3. Eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
428
0
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 376 publications
(456 citation statements)
references
References 172 publications
(752 reference statements)
13
428
0
15
Order By: Relevance
“…Another recently published trial found that deprescription protocols can be applied in frail elderly patients without adversely affecting their survival [1]. Patient-specific interventions are gaining evidence in mortality reduction effect [9] but more studies are needed to detect the influence of deprescription on multiple outcomes.…”
Section: Deprescriptions; Polypharmacy; Pharmacovigilance; Pharmacoepmentioning
confidence: 99%
“…Another recently published trial found that deprescription protocols can be applied in frail elderly patients without adversely affecting their survival [1]. Patient-specific interventions are gaining evidence in mortality reduction effect [9] but more studies are needed to detect the influence of deprescription on multiple outcomes.…”
Section: Deprescriptions; Polypharmacy; Pharmacovigilance; Pharmacoepmentioning
confidence: 99%
“…17 31 It was highlighted again in three more recent systematic reviews. 2,32,33 Deprescribing was defined as 'medication withdrawal in older people' in a 2008 systematic review of withdrawing individual medications. 31 Le Couteur et al clarified that this was the 'cessation of long-term therapy supervised by a clinician'.…”
Section: Use and Definition Of The Concept Deprescribingmentioning
confidence: 99%
“…It is challenging to reduce the total number of medications taken, but recent research has indicated it is feasible. 32,35 Adverse effects can prompt deprescribing. 35 Many people experience side effects of their medications that can range from mildly irritating to intolerable or life-threatening.…”
Section: Antecedents To Deprescribingmentioning
confidence: 99%
See 2 more Smart Citations